2015
DOI: 10.1016/j.bbmt.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Admission of Hematopoietic Cell Transplantation Patients to the Intensive Care Unit at the Pontificia Universidad Católica de Chile Hospital

Abstract: Patients undergoing hematopoietic cell transplantation (HCT) can have complications that require management in the intensive care unit (ICU). We conducted a retrospective study of patients undergoing HCT between 2007 and 2011 with admission to the ICU. We analyzed 97 patients, with an average age of 37 (range, 15 to 68). The main indications for HCT were hematologic malignancies (84%, n = 82). Ninety percent (n = 87) received myeloablative conditioning. Thirty-one percent were admitted (autologous transplant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
1
6
0
3
Order By: Relevance
“…RIC is endowed with more late complications or relapses than myeloablative allografting, and the timing of these complications may also be related to the differences observed between the groups reported from Denmark and Mexico. Even though the in-hospital mortality rate was higher in the Mexican group, the 1-year overall survival was better in the patients from Mexico and similar to that reported from Chile [5], another developing country. …”
supporting
confidence: 60%
“…RIC is endowed with more late complications or relapses than myeloablative allografting, and the timing of these complications may also be related to the differences observed between the groups reported from Denmark and Mexico. Even though the in-hospital mortality rate was higher in the Mexican group, the 1-year overall survival was better in the patients from Mexico and similar to that reported from Chile [5], another developing country. …”
supporting
confidence: 60%
“…A paper dealing with ICU admission after HSCT in a developing country (Chile) has been recently published [25] . Interestingly, the need to admit transplanted patients was in agreement with our experience (15% of autografts and 34% of allografts in their experience vs. 11 and 27%, respectively, in ours).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, their survival has improved, but mortality still remains high . The reported hospital mortality of patients in studies that were published after 2010 is in the range from 63% to 83% . Long‐term survival is uniformly poor, with reported 1‐year survival rates in recent publications ranging from 15% to 19% .…”
Section: Icu Referral Of Critically Ill Patients With Cancermentioning
confidence: 99%
“…[130][131][132][133] The reported hospital mortality of patients in studies that were published after 2010 is in the range from 63% to 83%. 127,131,[134][135][136][137] Long-term survival is uniformly poor, with reported 1-year survival rates in recent publications ranging from 15% to 19%. 131,134,138 Of note, a British retrospective, single-center study demonstrated that, despite the poor outcome of critically ill allogeneic stem cell transplantation recipients, those patients who did survive the ICU stay achieved impressive 1-year and 5-year survival rates of 61% and 51%, respectively, that were equivalent to those of transplant recipients who did not require ICU admission.…”
Section: Prognosis Of Critically Ill Patients With Cancermentioning
confidence: 99%